2021
DOI: 10.3389/fonc.2021.612009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Autophagy and Mitophagy Markers in Breast Cancer Tissues

Abstract: Mitochondria play important roles in regulating cell bioenergetics status and reactive oxygen species (ROS) generation. ROS-induced mitochondrial damage is among the main intracellular signal inducers of autophagy. Autophagy is a cellular catabolic process that regulates protein and organelle turnover, while a selective form of autophagy, mitophagy, specifically targets dysfunctional mitochondrial degradation. This study aims to measure the levels of autophagy, mitophagy, oxidative stress, and apoptosis in inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
4
6
0
Order By: Relevance
“…In addition to decreased mitochondrial function, we show that activation of mitophagy is a response to the decreased mitochondrial membrane potential (Figure 4A,B). Consistent with our results, previous research has reported that high LC3, PINK1 and p62 protein levels are associated with triple-negative BC (TNBC) patients and with poor response to chemotherapy, similar results have also been found in colorectal cancer, gastric, malignant melanoma, and esophageal cancer [54][55][56][57][58][59][60][61]. This demonstrates that deficiency of mitochondrial activity correlates with the invasiveness and metastatic capacity of the basal-like subtype of BC [62].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to decreased mitochondrial function, we show that activation of mitophagy is a response to the decreased mitochondrial membrane potential (Figure 4A,B). Consistent with our results, previous research has reported that high LC3, PINK1 and p62 protein levels are associated with triple-negative BC (TNBC) patients and with poor response to chemotherapy, similar results have also been found in colorectal cancer, gastric, malignant melanoma, and esophageal cancer [54][55][56][57][58][59][60][61]. This demonstrates that deficiency of mitochondrial activity correlates with the invasiveness and metastatic capacity of the basal-like subtype of BC [62].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrate that TFEB and CARM1 act as effectors of the autophagy process, and their significant correlation in our results confirms this [15]. Besides, SIRT1, CARM1, and TFEB positively correlated with Beclin-1, a known marker of the autophagy process [21]. Even by selecting only the luminal molecular subtypes, it emerges that the rho coefficient of the correlation between TFEB and CARM1 approaches significance (Supplemental Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…SIRT1 is known to be a significant prognostic factor in many cancers [18], and a high SIRT1 expression is known to be an unfavorable prognostic factor in breast cancer [19,20]. In addition, Beclin-1 is a known marker of autophagy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is currently assumed that ROS plays a dual role in malignancies. On the one hand, ROS can activate a variety of redox reactions and signaling pathways, such as the MAPK pathway, PI3K/AKT pathway, NF-κB pathway, and Keap1-Nrf2-ARE pathway, to promote tumor occurrence, development, and metastasis; on the other hand, when ROS exists in excess, it can cause cellular stress and damage through oxidative stress mechanism and eventually lead to cell death [62][63][64]. It all depends on the severity of the ROS excess and the duration of exposure; oxidative stress can activate cell survival or apoptosis mechanisms.…”
Section: Nosh-aspirin Increases Intracellular Rosmentioning
confidence: 99%